Consumer loyalty assessment as an important means of increasing company's profitability - Skryhun, Natalya; Kapinus, Larisa; Petrovych, Marharyta (My University, 2020)
The essence of consumer loyalty is revealed and substantiated and its value for companies is determined. The concept of loyalty, level of satisfaction is considered, the levels of loyalty and factors influencing consumer loyalty are distinguished, as well as methods of estimation of the degree of customer satisfaction are investigated. Розкривається та обґрунтовується сутність лояльності споживачів та визначається її цінність для компаній. Розглянуто поняття лояльності, рівня задоволеності, рівні лояльності та фактори, що впливають на лояльність споживачів, а також досліджуються методи оцінки ступеня задоволеності клієнтів.
Keywords: кафедра маркетингу; лояльність споживачів; поведінка споживача; consumer loyalty; customer behavior